2004
DOI: 10.1097/00002371-200403000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Analysis of a Phase I/II Study of Vaccination with MAGE-3 Protein Combined with the AS02B Adjuvant in Patients with MAGE-3-Positive Tumors

Abstract: In a phase I/II study, patients with solid metastatic MAGE-3-positive tumors, mainly melanoma, were vaccinated with recombinant MAGE-3 protein combined with the immunologic adjuvant AS02B comprised of MPL and QS21 in an oil-in-water emulsion. The recombinant MAGE-3 protein was made up of a partial sequence of the protein D (ProtD) antigen of Haemophilus influenzae fused to the MAGE-3 sequence. The vaccine was given intramuscularly at 3-week intervals. Patients whose tumors stabilized or regressed after 4 vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 44 publications
2
49
1
Order By: Relevance
“…We have also reported that absence of adjuvant in the vaccine during priming resulted in the failure of the vaccine to induce detectable antibody and T cell responses, an observation confirmed by others (42,43). Our study now demonstrates that immune memory was also persistent in patients primed with MAGE-A3 protein without an inflammatory adjuvant.…”
Section: Discussionsupporting
confidence: 86%
“…We have also reported that absence of adjuvant in the vaccine during priming resulted in the failure of the vaccine to induce detectable antibody and T cell responses, an observation confirmed by others (42,43). Our study now demonstrates that immune memory was also persistent in patients primed with MAGE-A3 protein without an inflammatory adjuvant.…”
Section: Discussionsupporting
confidence: 86%
“…Dendritic cell maturation was induced by using either CD40 agonistic antibodies (mouse IgG1, clone mAb89, Immunotech), or a lipopolysaccharide A analogue (31,32), monophosphoryl lipid A (MPL: detoxified lipid A derived from Salmonella; Avanti Polar Lipids, Inc.), chosen because both reagents have previously been approved for use in clinical trials (31 -35). Dendritic cells were cocultured with oxidized SK-OV-3 and then treated with CD40 antibody (100-1,000 ng/mL) or MPL (50-200 ng/mL) for 24 h at 37jC/5%CO 2 AIM-V CM.…”
Section: Methodsmentioning
confidence: 99%
“…One dose of the MAGE-A3 Cancer Immunotherapeutic consisted of 300 g recombinant MAGE-A3 antigen (ProteinD-MAGE-A3-His; recMAGE-A3) [41] and a fixed dose of the AS15 immunostimulant, containing MPL (GSK Vaccines, Rixensart, Belgium), QS-21 (Antigenics Inc, a wholly owned subsidiary of Agenus Inc., Lexington, MA, USA), CpG 7909 synthetic oligodeoxynucleotides containing unmethylated CpG motifs, and liposome (50 g MPL, 50 g QS-21 and 420 g CpG 7909). The control was a 0.9% sterile sodium chloride solution (saline).…”
Section: Test Itemsmentioning
confidence: 99%